Assessment of local government unit disparities and localization of performance and development indicators towards achievement of sustainable development - Pardo, Rashel Yasmin Z.
"Local governments have been exposed to performance and development measurement for several years; however, information culture is not yet fully in place. Financial burden and socio-political implications, brought about by the implementation of performance and development measurement, hamper the growth of local government units (LGUs) as performance and development-oriented units. The wide divergence of the fiscal characteristics of regions discussed in Chapter 4 signals not only regional imbalance, but also the need to review the existing systems for measuring performance and development, as standard approaches may not always be, partly or entirely, applicable to their diverse capacities and limitations. More importantly, the magnitude of the diversity among the regions provides a good basis for an examination at the local level. Indeed, it was not surprising that LGUs exhibited varying fiscal capacities and limitations. Specifically, the municipalities, cities and provinces showed much variation in their assessment of the degree of importance of local issues and concerns, LGUs of various levels, ecosystems and income classifications attach different ranks to different issues and concerns. Thus, given the uniqueness of local governments, detailed and precise indicators to measure performance and development are required.The analysis on the significance of performance and development indicators (PDIs) at the local level in Chapter 5 shows that LGUs find PDIs necessary in the achievement of sustainable development. However, costly implications; unsuitable indicators; and complex data requirement and method of analysis prevent them from properly and regularly implementing PDIs.